Utilização de um equipamento eletrônico como uma ferramenta didática para o ensino - Morais, Artênio Rocha de (Universidade Federal Rural do Semi-Árido, 2018)
The use of teaching kits is increasingly being used in undergraduate courses in order to improve teaching-learning and to confront with practice the knowledge seen in theory. One of the drawbacks of using these kits is that these are very expensive and often make your purchase unfeasible due to contention of university expenses. This work consists of the use of the didactic kit for practices of digital circuits, proposed by Teófilo (2015), as a way of continuing this work. This work will describe the composition and operation of this kit, the development of experiments carried out in the Multisim software and implemented in the kit with the purpose of making this work available for future use by professors of the Federal University of the Semi- Arid (UFERSA), Campus Pau dos Ferros. It is hoped with this work, to assist teachers and students in the use of this kit in the classroom, in order to contribute to the improvement of teaching-learning.
Keywords: kit didático; experimentos práticos; ensino-aprendizagem; teaching kit; practical experiments; teaching-learning; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA